2006
DOI: 10.1213/01.ane.0000246811.88524.75
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Versus Plethysmographic Dynamic Indices to Test Responsiveness for Testing Fluid Administration in Hypotensive Patients: A Clinical Trial

Abstract: In the present study, we compared indices of respiratory-induced variation obtained from direct arterial blood pressure measurement with analogous indices obtained from the plethysmogram measured by the pulse oximeter to assess the value of these indices for predicting the cardiac output increase in response to a fluid challenge. Thirty-two fluid challenges were performed in 22 hypotensive patients who were also monitored with a pulmonary artery catheter. Hemodynamic and plethysmographic data were collected be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 46 publications
6
89
2
1
Order By: Relevance
“…This study compared the relationship between SVV and PVI intraoperatively, which showed that SVV has a good agreement with PVI. This finding is in agreement with previous studies (7,18), which compared ΔPOP and ΔPP in mechanically ventilated patients under general more than 20% from preoperative values, and completed between 20 to 30 min. Hemodynamic measurements were performed before, and within 30 sec after volume expansion without stimulation, in order to limit changes in vasomotor tone that may have affected PVI value (14).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study compared the relationship between SVV and PVI intraoperatively, which showed that SVV has a good agreement with PVI. This finding is in agreement with previous studies (7,18), which compared ΔPOP and ΔPP in mechanically ventilated patients under general more than 20% from preoperative values, and completed between 20 to 30 min. Hemodynamic measurements were performed before, and within 30 sec after volume expansion without stimulation, in order to limit changes in vasomotor tone that may have affected PVI value (14).…”
Section: Discussionsupporting
confidence: 94%
“…Respiratory variation in the ΔPOP waveform amplitude has been studied in mechanically ventilated patients (18,22). Pleth variability index (PVI) (Masimo Co., Irvine, Canada) is a novel algorithm allowing for automated and continuous monitoring of ΔPOP (7).…”
Section: Changes In Hemodynamic Variables After Volume Expansionmentioning
confidence: 99%
“…Plethysomgraphic variability has been shown to predict fluid responsiveness in cardiac [30], general surgical [37] and intensive care patients [28], and goal directed fluid administration protocols directed by PVI have been shown effective at reducing morbidity and length of stay [27] [30] [38]. For dialysis-dependent patients, it is possible that the plethysmographic signal being used to calculate PVI may not be usable.…”
Section: Discussionmentioning
confidence: 99%
“…Because changes in the amplitude of the pulse oximeter plethysmograph correlate closely with variation in pulse pressure [26] [27]; the plethysmographic variability is able to predict fluid responsiveness in surgical pa-tients [28] [29]. PVI values greater than 13% have been shown to predict fluid responsiveness in surgical patients [30] [31].…”
Section: = ×mentioning
confidence: 99%
“…10,16 Pulse pressure variation (PPV) and systolic pressure variation (SPV)-both derived from analysis of the arterial waveform-, stroke volume variation (SVV), and the variation of the amplitude of the pulse oximeter plethysmographic waveform are predictive of fluid responsiveness. 7,21,22 These techniques use heart-lung interactions during mechanical ventilation. During inspiration, pleural pressure increases, causing a reduction in RV preload and an increase in RV afterload.…”
Section: Dynamic Variablesmentioning
confidence: 99%